Abundance trade-offs and dominant taxa maintain the stability of the bacterioplankton community underlying Microcystis blooms - Chen, Jun; Zhang, Tiange; Sun, Lingyan; Liu, Yan; Li, Dianpeng; Leng, Xin; An, Shuqing (Frontiers in Microbiology, 2023)
Microcystis blooms are an intractable global environmental problem that pollute water and compromise ecosystem functioning. Closed-lake management practices keep lakes free of sewage and harmful algae invasions and have succeeded in controlling local Microcystis blooms; however, there is little understanding of how the bacterioplankton communities associated with Microcystis have changed. Here, based on metagenomic sequencing, the phyla, genera, functional genes and metabolic functions of the bacterioplankton communities were compared between open lakes (underlying Microcystis blooms) and closed lakes (no Microcystis blooms). Water properties and zooplankton density were investigated and measured as factors influencing blooms. The results showed that (1) the water quality of closed lakes was improved, and the nitrogen and phosphorus concentrations were significantly reduced. (2) The stability of open vs closed-managed lakes differed notably at the species and genus levels (P<0.01), but no significant variations were identified at the phylum and functional genes levels (P>0.05). (3) The relative abundance of Microcystis (Cyanobacteria) increased dramatically in the open lakes (proportions from 1.44% to 41.76%), whereas the relative abundance of several other dominant genera of Cyanobacteria experienced a trade-off and decreased with increasing Microcystis relative abundance. (4) The main functions of the bacterioplankton communities were primarily related to dominant genera of Proteobacteria and had no significant relationship with Microcystis. Overall, the closed-lake management practices significantly reduced nutrients and prevented Microcystis blooms, but the taxonomic and functional structures of bacterioplankton communities remained stable overall.